Matthew studies today – a willingness to suspect and a willingness to listen - Aarde, Andries van (HTS teologiese studies, 2010)
The aim of the article is to describe the state of Matthean studies by means of Paul Ricoeur’s notion of the ‘hermeneutical arc’. The focus will be on the relationship of women in Matthew’s gospel to the male disciples. The article’s point of departure is that Matthean exegesis is at a crossroads. Pivotal to proceeding beyond the crossroads is the hermeneutical aspect of a willingness to suspect and a willingness to listen. Such a willingness includes suspicion with regard to outdated values explicitly advocated by the text and a genuine listening to unarticulated voices that remain hidden because of ideologies that render them inaudible. In the process of understanding, the focus should be on issues of morality rather than on the mere accumulation of knowledge. Seen from this perspective, the article provides a preview of facets in Matthean studies that could become prominent in future.